2003
DOI: 10.1002/icd.295
|View full text |Cite
|
Sign up to set email alerts
|

Infants' perception of directional alignment of texture elements on a spherical surface

Abstract: By appropriately compressing texture elements on a circular surface, one can evoke the impression of being confronted with the depiction of a spherical object in the picture plane. According to Todd and Akerstrom (1987), the 3D perception of such an object can be eliminated if the optical elements are not sufficiently elongated or if they are not aligned with one another. In the current investigation, 4-month-old infants were tested for their ability to react to a disruption of the directional alignment variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As noted earlier, other studies have found that young infants are sensitive to information in pictorial displays that, to adults, create the impression of depth or 3-D structure Bhatt & Waters, 1998;Durand & Lécuyer, 2002;Durand et al, 2003;Imura et al, 2004;Kavnek, 2003b;Lécuyer & Durand, 1998). For example, Imura and colleagues (2004) used a paired-comparison procedure and popout stimuli and found that 4-month-olds were able to discriminate a vertical change in shading direction signaled by pictorial cues.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As noted earlier, other studies have found that young infants are sensitive to information in pictorial displays that, to adults, create the impression of depth or 3-D structure Bhatt & Waters, 1998;Durand & Lécuyer, 2002;Durand et al, 2003;Imura et al, 2004;Kavnek, 2003b;Lécuyer & Durand, 1998). For example, Imura and colleagues (2004) used a paired-comparison procedure and popout stimuli and found that 4-month-olds were able to discriminate a vertical change in shading direction signaled by pictorial cues.…”
Section: Discussionmentioning
confidence: 85%
“…For example, Kavnek (2003b) familiarized 4-month-olds with computer animations of circular displays with texture elements that were arranged to evoke the impression of either a sphere or a Xat disc. Subsequently, he tested infants' ability to discriminate the spherical and Xat displays.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, sex differences have been reported in several other domains, including habituation behaviors (Creighton, 1984;Tighe & Powlison, 1978), perception of pictorial cues (Kavšek, 2003(Kavšek, , 2004, categorization (Arterberry & Bornstein, 2002), imitation of propulsive motion (Benenson, Tennyson, & Wrangham, 2011), perception of number (Moore & Cocas, 2006;Strauss & Curtis, 1981), and components of linguistic processing (Friederici et al, 2008;Lany & Gomez, 2008;Shucard, Shucard, & Thomas, 1987). However, many of these results are difficult to interpret, have not been replicated, and/or have inconsistent outcomes across studies.…”
Section: Cognitive Behaviormentioning
confidence: 99%
“…Several experiments employing habituation–dishabituation methods have supported the conclusion that there is an increase in sensitivity to pictorial depth cues with age (Arterberry et al., 1991; Imura et al., 2006; Kavšek, 1999, 2009; Oross et al., 1987). Other habituation–dishabituation studies, however, suggest that 3‐ to 4‐month‐old infants are capable of perceiving pictorial depth (Bertin & Bhatt, 2006; Bhatt & Bertin, 2001; Bhatt & Waters, 1998; Durand & Lécuyer, 2002; Durand, Lécuyer, & Frichtel, 2003; Imura, Tomonaga, Yamaguchi, & Yagi, 2004; Kavšek, 2003b; Putaansuu & von Hofsten, 1991; Shuwairi, 2009; Shuwairi, Albert, & Johnson, 2007; Yonas, Granrud, Le, & Forsyth, 2007). For example, in a study that explored the “pop‐out” effect, Bertin and Bhatt (2006) found that 3‐month‐olds are sensitive to line junction cues.…”
mentioning
confidence: 99%
“…It is possible that these studies detected pictorial depth perception in young infants because they used more sensitive experimental methods and/or more compelling displays. For example, embedding pictorial cues to depth in a dynamic display (e.g., Kavšek, 2003b) or in a pop‐out pattern (e.g., Bertin & Bhatt, 2006) might generate a stronger depth effect and improve the likelihood that younger infants will respond to these cues.…”
mentioning
confidence: 99%